Secukinumab in enthesitis-related arthritis and juvenile psoriatic arthritis: a randomised, double-blind, placebo-controlled, treatment withdrawal, phase 3 trial. Issue 1 (12th August 2022) - Brunner, Hermine I; Foeldvari, Ivan; Alexeeva, Ekaterina; Ayaz, Nuray Aktay; Calvo Penades, Inmaculada; Kasapcopur, Ozgur; Chasnyk, Vyacheslav G; Hufnagel, Markus; Żuber, Zbigniew; Schulert, Grant; Ozen, Seza; Rakhimyanova, Adelina; et al.
Abstract : Background: Treatment options in patients with enthesitis-related arthritis (ERA) and juvenile psoriatic arthritis (JPsA) are currently limited. This trial aimed to demonstrate the efficacy and safety of secukinumab in patients with active ERA and JPsA with inadequate response to conventional therapy. Methods: In this randomised, double-blind, placebo-controlled, treatment-withdrawal, phase 3 trial, biologic-naïve patients (aged 2 to <18 years) with active disease were treated with open-label subcutaneous secukinumab (75/150 mg in patients <50/≥50 kg) in treatment period (TP) 1 up to week 12, and juvenile idiopathic arthritis (JIA) American College of Rheumatology 30 responders at week 12 were randomised 1:1 to secukinumab or placebo up to 100 weeks. Patients who flared in TP2 immediately entered open-label secukinumab TP3 that lasted up to week 104. Primary endpoint was time to disease flare in TP2. Results: A total of 86 patients (median age, 14 years) entered open-label secukinumab in TP1. In TP2, responders (ERA, 44/52; JPsA, 31/34) received secukinumab or placebo. The study met its primary end point and demonstrated a statistically significant longer time to disease flare in TP2 for ERA and JPsA with secukinumab versus placebo (27% vs 55%, HR, 0.28; 95% CI 0.13 to 0.63; p<0.001). Exposure-adjusted incidence rates (per 100 patient-years (PY), 95% CI) for total patients were 290.7/100 PY (230.2 to 362.3) for adverse events and 8.2/100 PY (4.1 to 14.6) for serious adverse events in the overall JIA population. Conclusions: Secukinumab demonstrated significantly longer time to disease flare than placebo in children with ERA and JPsA with a consistent safety profile with the adult indications of psoriatic arthritis and axial spondyloarthritis. Trial registration number: NCT03031782 .